2013
DOI: 10.3892/or.2013.2737
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and prognostic value of osteopontin and Bcl-2 in hepatocellular carcinoma patients after curative resection

Abstract: Abstract. Osteopontin (OPN) may facilitate tumorigenesis and metastasis through prevention of tumor cells from apoptosis. Although previous studies have suggested involvement of enhanced Bcl-2 protein family expression, the role of OPN together with Bcl-2 in hepatocellular carcinoma (HCC) remains unknown. In this study, we used western blotting to detect the OPN and Bcl-2 expression levels in cell lines with different OPN backgrounds and HCC tissues, and tumor tissue microarrays to examine OPN and Bcl-2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…In the present study, the protein expression levels of caspase-3 and caspase-9 were significantly upregulated in the GnT-V-knockdown SMMC-7721/R cells, which was consistent with the results of a previous study performed in H7721 human HCC cells (21). Furthermore, the proteins Bcl-2 and Bax are also essential for cell apoptosis, functioning as the predominant controller and mediator of apoptosis, respectively, and the ratio of Bcl-2 to Bax is a key factor determining whether the switch to apoptosis is made (24,25). The results of the present study demonstrated that the protein expression level of Bcl-2 was downregulated, whereas that of Bax was upregulated.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the protein expression levels of caspase-3 and caspase-9 were significantly upregulated in the GnT-V-knockdown SMMC-7721/R cells, which was consistent with the results of a previous study performed in H7721 human HCC cells (21). Furthermore, the proteins Bcl-2 and Bax are also essential for cell apoptosis, functioning as the predominant controller and mediator of apoptosis, respectively, and the ratio of Bcl-2 to Bax is a key factor determining whether the switch to apoptosis is made (24,25). The results of the present study demonstrated that the protein expression level of Bcl-2 was downregulated, whereas that of Bax was upregulated.…”
Section: Discussionsupporting
confidence: 90%
“…Also patients with higher OPN levels had significantly shorter median survival time and recurrence time compared to the ones with lower OPN levels. It was also observed that co-index of OPN/Bcl-2 levels was an independent prognostic factor for both overall survival and time to recurrence in this cancer type (Deng et al, 2013). …”
Section: Opn In Clinical Evaluationsmentioning
confidence: 94%
“…They identified 6 proteins that were uniquely upregulated in early recurrence that included extracellular signal‐regulated kinase 1 (ERK1), protein kinase G (PKG), apoptotic protease activating factor 1 (Apaf1), B‐cell leukemia X (Bcl‐X), Abelson murine leukemia viral oncogene (c‐abl), protein inhibitor of activated STAT 1 (PIAS1), and PIAS2. It has been demonstrated that both ERK and Bcl‐X correlate with a poor prognosis in HCC . Multiple ERK inhibitors are currently in early phase clinical trials for solid gastrointestinal malignancies and may be of potential value in the treatment of HCC.…”
Section: Hcc Proteomics Predict Prognosis and Identify Novel Treatmenmentioning
confidence: 99%
“…It has been demonstrated that both ERK and Bcl-X correlate with a poor prognosis in HCC. 94,95 Multiple ERK inhibitors are currently in early phase clinical trials for solid gastrointestinal malignancies and may be of potential value in the treatment of HCC.…”
Section: Hcc Proteomics Predict Prognosis and Identify Novel Treatmenmentioning
confidence: 99%